2001
DOI: 10.1007/s100240010145
|View full text |Cite
|
Sign up to set email alerts
|

Asplenic-hyposplenic Overwhelming Sepsis: Postsplenectomy Sepsis Revisited

Abstract: Absence of the spleen or splenic function predisposes individuals to risk of overwhelming infection. These infections are most often due to encapsulated organisms, especially pneumococcus, Haemophilus influenzae type b, and meningococcus, but any bacterial agent may cause the rapid onset of septicemia, meningitis, pneumonia, and shock characteristic of the asplenic-hyposplenic condition. The risk is greatest in infants and young children, but asplenic-hyposplenic adults also have an increased risk of infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
135
1
27

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(165 citation statements)
references
References 88 publications
2
135
1
27
Order By: Relevance
“…The immunological consequences of splenectomy [5,6] and the realization that most splenic injuries stop bleeding spontaneously in the vast majority of cases created the impetus for nonoperative management, which is now the standard of care [7]. The current recommendation of bed rest equaling 1 day plus the grade of injury has recently been reviewed, and an attenuated protocol has been recommended for hemodynamically stable patients to facilitate concise utilization of health care resources [8].…”
Section: Discussionmentioning
confidence: 99%
“…The immunological consequences of splenectomy [5,6] and the realization that most splenic injuries stop bleeding spontaneously in the vast majority of cases created the impetus for nonoperative management, which is now the standard of care [7]. The current recommendation of bed rest equaling 1 day plus the grade of injury has recently been reviewed, and an attenuated protocol has been recommended for hemodynamically stable patients to facilitate concise utilization of health care resources [8].…”
Section: Discussionmentioning
confidence: 99%
“…Its functions can be divided into four main groups, such as filtration, immunological, storage and haemopoietic functions. Recent studies have showed its role in lipid-metabolism, too [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical practice the early and late complications following splenectomy have been known for a long time 2,7,8 , but the explanation for the late complications was given only by recent research on spleen surgery and spleen-sparing operations 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic antibiotics and immunization with polyvalent Pneumococcal, H. infl uenzae type b, and Meningococcal vaccines have reduced the incidence of infections in asplenic individuals, but even these measures have not eliminated the risk. Therapies designed to interrupt the cascade of overwhelming sepsis have not yet been successful (13,19,23,30,37) . Since 1985, we had performed at minimum 250 EGDS in "Santa Casa" Medical School, Surgery Department, São Paulo, SP, Brazil.…”
Section: Introductionmentioning
confidence: 99%